Promoting Quality Education by digitally transforming the techniques; A Literature Review - Sagar Samy (International Journal on Integrated Education, 2022)
Education plays an important role in every society, in order to uplift any country education must be spread out to the masses. Hence, the right to education is documented as a Human Right. To make it sustainable, the United Nations is promoting Sustainable Development Goals i.e., Quality Education. The challenges and outcomes to overcome while achieving Quality Education in Pakistan have been discoursed in this study. Henceforward, education is the only tool that cannot only change the fate of 65% youth of the country but also can help Pakistan to boost up and benefit to be a developed nation. To promote quality education, the nation must adopt all the modern techniques of technology, as the entire paradigm is rapidly shifting or has already shifted after the COVID-19 pandemic. The west and the first world countries continued to rise because they are investing more and more in education, along with integrating all the modern and latest techniques of technology. In fact, the future is now, developed countries have started working on metaverse to transform the entire education system in the coming years. The study is a literature review and descriptive which is based on secondary sources like books, research articles, website content, and reports. Henceforth, the findings show that Quality education can act as a revolutionary tool to change the fate of Pakistan.